THE ROLE OF MOTIVATION, COMMUNICATION, AND WORK STRESS ON EMPLOYEE JOB SATISFACTION - Khafid, Abdul; Eka Kurnia Patmasari (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
This study aims to analyze and provide empirical evidence regarding the influence of motivation, communication, and work stress on employee job satisfaction at CV Wiflas Putra Semarang. The variables of motivation, communication, and work stress are designated as independent variables, while job satisfaction is the dependent variable. Data collection was conducted through the distribution of a Google Forms-based questionnaire to the company's employees. The sampling technique used was purposive random sampling with a total of 100 respondents. The analysis method used is a quantitative approach with multiple linear regression. The results show that motivation and communication have a positive and significant effect on employee job satisfaction. Meanwhile, work stress is still at a manageable level, although it does not show an effect on job satisfaction. Simultaneously, motivation, communication, and work stress influence employee job satisfaction, with motivation being the most dominant variable. These findings suggest that the management of CV Wiflas Putra Semarang needs to strengthen its work motivation program through a reward system, career development opportunities, and constructive performance feedback. Furthermore, management needs to establish a more open, structured, and two-way internal communication pattern to minimize miscommunication and increase employee engagement. Workplace stress management also needs to be implemented through workload management, role clarity, and a supportive work environment to ensure stress levels remain within productive limits, thereby maintaining and improving employee job satisfaction.